Understanding perceived performance impacts of mobile phone use among smallholders in Uganda: the influence of task-technology fit and current use - Aparo, Nathaline Onek; Atimango, Alice Onek; Odongo, Walter; De Steur, Hans (Cogent, 2024)
This study evaluated the factors influencing the perceived performance impact (PPI) of mobile phone use in agriculture. Based on the Technology-to-Performance chain (TPC) model, an interviewer-administered cross-sectional survey was conducted among 250 smallholder farmers in Uganda. Descriptive statistics were generated in SPSS to characterise the respondents and partial least squares structural equation modelling (PLS-SEM) was conducted in SmartPLS 4 to predict the hypothesised relationships. The results show that both perceived task Technology fit (PTTF) and current mobile phone use predict PPI, with PTTF being a stronger predictor of PPI. PTTF is best explained by task characteristics, while respondents' current mobile phone use is strongly influenced by social norm. This study advances the TPC model and contributes to understanding the factors and strategies that can be leveraged to enhance perceived performance impacts of mobile phones among smallholders. They are useful for researchers, policy makers, mobile phone application developers and agricultural practitioners.